KEBENCIAN TERHADAP RAS ASIA DI AMERIKA SERIKAT SAAT PANDEMI COVID-19 DITINJAU DARI HUKUM HAK ASASI MANUSIA INTERNASIONAL: RACIAL HATRED TOWARDS ASIANS IN THE U.S DURING THE COVID-19 FORM THE PERSPECTIVE OF INTERNATIONAL HUMAN RIGHTS LAW - Dien, Carla Olivia Permana; Nrangwesti, Ayu (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2025)
Crimes against humanity targeting Asian races in various regions of the world, including in the United States during the Covid-19 pandemic, have raised concerns. Numerous cases of racial crimes involving Asians as victims of violence have resulted in serious injuries and even loss of life. The legal issue discussed is the forms of human rights violations against Asians during the Covid-19 pandemic in the United States and the measures taken by the U.S. government to address these issues from the perspective of International Human Rights Law, such as the ICCPR and The Civil Rights Act. Racial discrimination and attacks against Asians undermine the right to life and individual security. Therefore, the U.S. government has acted to uphold the principles of International Human Rights by implementing stricter law enforcement measures to respond to discriminatory acts and racial hatred, allocating funds for victim recovery, and establishing a special task force to combat xenophobia against Asians in healthcare services. These efforts aim not only to achieve justice for victims but also to prevent future human rights violations